Pengaruh Tarif Pajak, Sosialisasi Pajak, E-Filling dan Pengetahuan Perpajakan pada Wajib Pajak Orang Pribadi terhadap Kepatuhan Wajib Pajak: Survey pada Wajib Pajak Orang Pribadi di KPP Pratama Jakarta Pluit - Kesuma, Wijaya; Halim, Sofyan (JUDICIOUS, 2023)
Tax revenue growth is still below expectations. Low tax rates in Indonesia resulting in low per capita income, low levels of taxpayer compliance, and other factors reflect this. This study aims to determine the effect of tax rates, tax socialization, e-filing, and tax awareness on individual taxpayer compliance at KPP Pratama Jakarta Pluit. This research uses a direct random sampling technique based on the Slovin formula. Research findings show that socialization and tax knowledge influence taxpayer compliance. Primary data used in the research was collected from 100 individual taxpayers through distributing questionnaires. The findings from this study indicate that tax rates and electronic filing have no impact on taxpayer compliance. Taxpayer compliance in paying taxes can be influenced by factors of tax socialization and tax knowledge made to taxpayers. This has a positive impact on taxpayer compliance. Several other variables in this research, such as E-filling, actually have no effect on taxpayer compliance with paying taxes